Band Structure, Band Offsets, and Intrinsic Defect Properties of Few-Layer Arsenic and Antimony - Yuzheng Guo (The Journal of Physical Chemistry C, 2020)
We present a detailed first-principle study of few-layer arsenic and antimony electronic structures. The band structures of 2D arsenic and antimony are calculated by a hybrid functional with the spin–orbital coupling. The results show that the band gaps of arsenene (monolayer arsenic) and antimonene (monolayer antimony) are 1.93 and 1.52 eV, respectively. It is observed that the band gaps narrow in trilayer arsenic and bilayer antimony. The band alignment with HfO2 and other 2D materials is calculated to show that HfO2 is a good candidate as a gate oxide in field effect transistors. It is found that point defects such as a single vacancy or adatom will introduce several defect states in arsenene in the middle of the band gap. Meanwhile, the defect formation energy becomes negative when the Fermi level is close to the band edges. By comparison, the defect formation energy in antimonene is always positive so that the Fermi level pinning should be suppressed in contact with the reactive metal.